Penggunaan Partikel ã§ dan ã« Oleh Mahasiswa Program Studi Sastra Jepang Universitas Hasanuddin Makassar - Imelda, Imelda (Lingua Cultura, 2013)
Japanese language is a language that has different sentence structure with bahasa Indonesia. In addition, particlesÂ or åŠ©è¯ are also characteristis in Japanese. There are so many of them, causing the basic level Japanese language learners confused. Therefore, as a new study program, studies based on goyou or dai ni gengou shuutoku are conducted as a mean to look at the problems occured in Japanese language learning at UNHAS. This study used qualitative researchmethod. Population was taken from Japanese Literature, Faculty of Literature, Universitas Hasanuddin. Twenty two from second year students were the sample and randomly selected. Based on the results, the research concludes that the explanation of the use of particleã§ and ã« in Minna No Nihongo I was not all covered, especially on particle ã« . The explanation of the use of particle ã«, especially verb ä½ã‚“ ã§ ã„ ã¾ã™, å…¥ã‚Š ã¾ã™, ä¹—ã‚Š ã¾ã™, is very prone to errors. This is due to the verb is unfamiliar or infrequently used by respondents in the sentence. Therefore, teachers can fill insufficient explanation in the book, so that the error can be minimized. Whereas, errors/goyou occurredÂ on particle ã§ are more on the functions of the particle for the scope, places of activities, and abstract tools.